An Investigation into the Nexus between Fiscal Policy, Foreign Direct Investment and Economic Growth in Nigeria - OLOGBENLA, Patrick (Journal of Social and Development Sciences, 2022)
The study examined the relationship between foreign direct investment and fiscal policy and the implication of the relationship on the Nigerian economic growth, the years under review were 1980 to 2019. Variables such as government expenditure, government revenue among others were used to proxy fiscal policy while data on foreign direct investment were used for FDI. The GDP growth rate was used as a proxy for the Nigerian economic growth. The study applied Autoregressive Distributed Lags estimating techniques. The result from the analysis indicated that the association between foreign direct investment and fiscal policy could not have a significant effect on the economic growth of Nigeria in the long run but, in the short run, the association was significant. The study recommends more collaboration between fiscal policy and foreign direct investment in such a way that it will promote the growth of the Nigerian economy.